Persuasive Impact Of Fit Between Regulatory Focus And Message Framing On Consumer Responses: Message Strength And Choice For Others - Choi, Jieun (Journal of Applied Business Research, 2018)
Previous research on message framing has argued that fit between message framing and consumer regulatory focus influences consumer response. That is, positive frames are more persuasive for promotion-focused individuals, while negative frames are more persuasive for prevention-focused individuals. This research aims to expand the scope of previous research on message framing and argues that the match-up effect between message framing and regulatory focus, an effect established in previous research, is dependent on the strength of the message. This research further argues that the match-up effect patterns between message framing and regulatory focus differ based on whether or not consumers are making a purchase for themselves or for others. Specifically, this research hypothesizes that prevention-focused individuals tend to focus on uncertainty or risks related to choice for others and exhibit low levels of purchase intention regardless of message framing under the condition of making a purchase for others. This research also proposes that promotion-focused individuals tend to focus more on potential positive outcomes rather than negative risks when making a choice for others, resulting in a higher purchase intention regardless of message framing. That is, under the condition of making a purchase for others, the match-up effect of message framing and regulatory focus is rendered void. This research expands the scope of existing research on message framing and provides practical implications for marketing practitioners.
Keywords: Message Framing; Regulatory Focus; Promotion Focus; Prevention Focus; Message Strength; Choice for Others